Pengaruh dan Pemikiran Muhammad Natsir (1908-1993) Dalam Pendidikan Islam Zaman Kolonial Belanda di Indonesia: Muhammad Natsir’s (1908-1993) Influences and Thoughts in Islamic Education During the Dutch Colonial Period in Indonesia - Mohamad Noor, Mohamad Muzammil (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
The article discusses Muhammad Natsir’s thoughts on Islamic education which influenced his involvement in the struggles of nationalism and politics in Indonesia. Natsir was the leader of the largest Islamic political organisation in the Southeast Asian region of the Masyumi Party. This writing will perceive how the foundations of his education have influenced his thoughts and struggle to uphold modern religious knowledge and education to the Muslim community. The findings showed that his thoughts had influenced the Indonesian Muslim community on Islamic knowledge that was always challenged by the Dutch colonialists. In addition, Natsir’s thoughts and struggles were expressed through his writings, his speeches, and the impact of what he had moulded by the establishment of his own religious school in Bandung, PENDIS. Through his writings, he emphasized the importance of modern education and Islamic knowledge to his colonised society. As a result of this writing, tracing the understanding of his thoughts and struggles in developing Indonesian society through Islamic education is feasible but inevitable from religious-nationalism aspects of independence from the grasp of colonialists. This writing utilized a qualitative approach by conducting analysis through sources written by Natsir and several religious writers from Indonesia and Malaysia.